Chiral ruthenium(ii) complex as potent radiosensitizer of 125I through DNA-damage-mediated apoptosis. Issue 37 (6th June 2018) - Bai, Mingjun; Zeng, Zhaolin; Li, Li; Wu, Qiong; Zhang, Yanyang; Pan, Tao; Mu, Luwen; Zhu, Duo; Guan, Shouhai; Xie, Qiang; Mei, Wenjie
Abstract : SyntheticLR042 can be further developed as a radiosensitizer of 125 I by inducing DNA-damage-mediated apoptosis for cancer therapy. Abstract : A chiral ruthenium(ii ) complex, Λ-[Ru(bpy)2 ( o -tFMPIP)] (ClO4 )2 ( o -tFMPIP = 2′-trifluoromethylphenyl) imidazo [4, 5- f ][1, 10]phenanthroline, was prepared and evaluated for its enhancement of the radiosensitivity of 125 I seeds. The synthetic Ru(ii ) complex, LR042, effectively enhanced growth inhibition against HepG2 human hepatocellular liver carcinoma cells induced by 125 I seeds and consequently effectively promoted the apoptosis of tumor cells with increasing level of cleave-caspase-3. Furthermore, the results of immunofluorescence indicated thatLR042 enhanced the phosphorylation of H2AX by 125 I seeds vigorously in response to damaged DNA.LR042 improved DNA damage induced by 125 I seeds, which resulted in apoptosis through the activation of the p53/AKT signal. In conclusion, syntheticLR042 can be further developed as a potential radiosensitizer of 125 I seed radiotherapy for cancer therapy.